STABILOMETRIC METHODS FOR TESTING AND TRAINING OF HUMAN BODY BALANCE - V. A. Dubovsky (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The methods for the rehabilitation of patients with neurological disorders based on an unstable platform with audio-visual feedback of the support surface inclination are proposed. They allow the patients to train their ability to control center of gravity during specific dynamic tasks such as maintaining equilibrium, quick reaction, movement reproduction, rhythm synchronization, and simultaneous execution motor and cognitive tasks. A new postural control training system for patients with neurological disorders has been developed. This system equipped with audio-visual feedback of the support surface inclination and provides a complex approach to improving control of posture in subjects with motor and cognitive disorders.